PENGARUH KARAKTERISTIK, SIKAP, DAN KETERAMPILAN WIRAUSAHAWAN RUMAH MAKAN PEMPEK DI KOTA PALEMBANG TERHADAP KEBERHASILAN USAHA - Andreas Sarjono; M.J Tyra (Jurnal Keuangan dan Bisnis, 2019)
A study entitled “The Influence of Characteristics, Attitude and Skill of Pempek Entrepreneurs in Palembang toward Successful Business Achievement” is an entrepreneurship study related to the influencing factors of succesful business achievement of pempek entrepreneurs in Palembang. This purpose of this study is to find out whether or not the entrepreneurs’ characteristics, attitude and skill factors affect the succesful business achievement. Sample was selected by using purposive sampling technique. The hypothesis was tested by using multiple regression analysis. The t-test of SPSS calculation implied that the significant value of characteristics was 0.709, attitude was 0.213 and entrepreneurship skill was 0.287 (less than 0.05). Therefore, the results of the study implied that there was no correlation between characteristics, attitude and entrepreneurship skill of pempek entrepreneurs in Palembang toward succesful business achievement